Efek Kecakapan Profesional Guru dan Lingkungan Belajar Terhadap Hasil Belajar Siswa - Pande, Samsul; Sudiyono; Cicilia, Ika (Jurnal Penelitian dan Pendidikan IPS, 2023)
The purpose of this study was to analyze the effect of the teacher's professional skills and the learning environment on student learning outcomes. The study used a survey method with 286 high-class students at SDN Gugus Bumi Nickel, Bahodopi, Morowali as subjects. The data collection instrument was a questionnaire which was validated by the Cronbach Alpha test. Data analysis using multiple linear regression and t test. Analysis prerequisite tests include tests: normality, linearity, homogeneity, and autocorrelation. The results of the regression analysis obtained the value of F = 2609,473, sig = 0.000 (<0.05), the value of determination (R square) = 0.949, indicating that the professional skills of teachers and the learning environment simultaneously affect student learning outcomes by 94.9%, the remaining 5, 1% is influenced by other variables outside of this study. The first t test obtained a value of t = 3.691 with Sig = 0.000 (<0.05) meaning that partially there is an influence of the teacher's professional skills on student learning outcomes. The second t test obtained a value of t = 63,545, sig = 0.000 (<0.05), meaning that partially there is an influence of the learning environment on learning outcomes. Conclusion: (1) Simultaneously there is an influence of the teacher's professional skills and the learning environment on student learning outcomes. (2) Partially, there is an influence of the teacher's professional skills on student learning outcomes. (3) Partially there is the influence of the learning environment on student learning outcomes